Minimizers of a functional of the gradient, which are stable with respect to affine boundary data - Goncharov, Vladimir (2011)
We study the family of minimizers of an integral functional of the gradient over all Sobolev functions, which have a constant gradient v on the boundary, and give some results (including a category theorem) on continuous dependence of such minimizers on the vector v with respect to the uniform topology.